Internet Use Pattern among the Students in Annamalai University - Manimekalai, A.; Balasubramani, R.; Amsaveni, N. (Journal of Information and Knowledge, 2006)
The use of Internet is an inevitable part and there is increasingly centered effect on the part of Government, Education Ministry to fulfill the special needs of the students. The extent and pattern of usage of the Internet amongst students in Annamalai University is the primary focus of this study. This study investigates the relationship between motivational variables (intrinsic and extrinsic), demographic variable and the Internet usage activities (messaging, downloading, browsing and purchasing). The finding also shows that perceived usefulness is an important driver of Internet usage.